شمائل نبویﷺکے بیان میں علامہ دمیاطیؒ کا منہج وأسلوب: Methadology of Allama Dimyati in Describing Appprantal Biography of Muhammadﷺ - Wisaal Ahmad; Hafiz Saif ur Rehman (Seerat Studies, 2023)
Biography of Holy Prophetﷺis an alive and brilliant topic.Many muslims and non muslims biographers from the first century till now were presented their researches on different angles of the personality of Prophetﷺ.According to basic resources, biography contain many types.One of them is the methodology of the narrators of Ahadith They collect material from Quran and Ahadith and introduced literary biography.One of the most famous biographer,narrator and commentary of Hadith from 7th century among them was Abdul Momin bin Khalf bin Sharaf Uddin Dimyati(614-705).He compiled his comprehensive book "المختصر فی سیرۃ سید البشر"on the biography of Holy Prophetﷺ according to narrators methodology.In this book,Allama Dimyati has described the features and characteristics of Prophet in the light of the main sources,Quran and Ahadith Nabviﷺ.He collects material from basic resources and comprehensive Ahadith.In this paper,the material realted to apparent biography of Prophet ﷺhas been analysed.